2004
DOI: 10.1063/1.1640331
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic-liquid crystalline phase diagram of a CdSe nanorod solution

Abstract: We report the isotropic-liquid crystalline phase diagram of 3.0 nm × 60 nm CdSe nanorods dispersed in anhydrous cyclohexane. The coexistence concentrations of both phases are found to be lower and the biphasic region wider than the results predicted by the hard rod model, indicating that the attractive interaction between the nanorods may be important in the formation of the liquid crystalline phase in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…due to solvent evaporation), because the gain in positional entropy on alignment (associated with reducing the total excluded volume) more than compensates for the loss in rotational entropy 24 . Li et al have observed similar liquid-crystalline behavior for CdSe nanorods 25 , which have analogous physical properties to the CdS nanorods used in the present study. In Li's work, the isotropic-nematic phase boundary was found to be weakly temperature dependent over the range considered (some of this data is plotted in Figure 3a for comparison), indicating that the entropically driven ordering may be opposed by enthalpic interactions that become less important at higher temperature.…”
supporting
confidence: 80%
“…due to solvent evaporation), because the gain in positional entropy on alignment (associated with reducing the total excluded volume) more than compensates for the loss in rotational entropy 24 . Li et al have observed similar liquid-crystalline behavior for CdSe nanorods 25 , which have analogous physical properties to the CdS nanorods used in the present study. In Li's work, the isotropic-nematic phase boundary was found to be weakly temperature dependent over the range considered (some of this data is plotted in Figure 3a for comparison), indicating that the entropically driven ordering may be opposed by enthalpic interactions that become less important at higher temperature.…”
supporting
confidence: 80%
“…Beside van der Waals interactions, the effects of electrostatic interactions were studied. 38,39 Furthermore, attractive interactions between the spherocylinders by depletion forces were considered by Bolhuis et al 40 Attractive interactions support the parallel orientation of the rods, so that the anisotropic phase starts to appear already at lower volume fractions as observed by Li et al 35 Bolhuis and…”
Section: Phase Transition Compared To Theory and Experimentsmentioning
confidence: 92%
“…34 Lower volume fractions for phase transitions are calculated by other groups. [35][36][37][38][39][40] In this study we combine in situ SAXS to study structure formation with ex situ SEM-based image analysis and Raman analysis. This allows us to tailor highly ordered nematic thin films by influencing the relative impact of the resulting evaporationinduced convective flow and externally applied shear forces.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al [98] demonstrated that by controlling the growth kinetics the shapes of the resulting cadmium selenide nanoparticles can be tuned to vary from a nearly spherical morphology to a rod-like one, with aspect ratios as large as 10 to 1. Li et al [99,100] observed the formation of a nematic LC phase in suspensions of these CdSe semiconductor nanorods. Smectic-like LC structures mediated by drying-induced self-assembly on a TEM grid were observed for CdSe nanorods by Li & Alivisatos [101] and for CdSe/CdS heteronanorods by Carbone et al [97], while Talapin et al [102] took the drying-induced selfassembly method one step further to produce highly luminescent smectic three-dimensional structures of CdSe and CdSe/CdS.…”
Section: (A) Novel Colloidal Liquid Crystal Phases In External Fieldsmentioning
confidence: 99%